Functional analysis of peripheral blood leucocytes of snakes (Boidae and Viperidae) during the process of adaptation to captivity - Carvalho, Marcelo Pires Nogueira de (2018)
Inflammatory processes are known to protect vertebrates from injuries and infections. However, from an immunological perspective the role of leukocytes in snakes inflammatory process is poorly understood. Within this context, leukocyte classification in these animals is not clearly defined, with authors disagreeing on existent cell types and their classification. Due to the great variation of snakes leukocytes on cytochemistry, an analysis focused exclusively on optical morphology is insufficient to determine different cell types. Thus, additional methods, as flow cytometry, are important to better understand the function and origin of each cell type. In particular, studies of chronic stress induced by captivity in reptiles demonstrate that serum corticosterone levels rise during the adaptation period and are associated with immune suppression. However, it is not known how the leukocyte functions of reptiles are altered under these conditions. The objective of this research was to adapt leukocyte density gradients (ficoll and percoll) for snake blood samples, and characterize recovered cells based on size, presence of granules and internal complexity (organelle), and on their cellular innate functions (oxidative burst and phagocytosis), in front of bacterial, fungal and chemical challenges, by flow cytometry; enabling the qualitative and quantitative assessment of innate activities presented by cells constituting the immune system of Boa constrictor, Bothrops jararaca and Crotalus durissus. Additionally, the study proposes to correlate innate leukocyte functions performances with serum corticosterone concentrations, in recent wild-caught viperids (B. jararaca and C. durissus), at two moments of adaptation to captivity (5 and 60 days of captivity). Comparison between gradient methods for leukocyte isolation did not show any statistical difference in types and proportion of leukocytes populations between snakes of the same species. When verified by means of flow cytometric cell sorting and confirmed by optical microscopy, populations were mainly composed of azurophils, heterophils, large lymphocytes and small lymphocytes. Concerning innate leukocyte functions, heterophils, lymphocytes and azurophils were involved in the phagocytosis response. Regarding oxidative burst activity, only azurophils presented a significative and strong oxidative burst when compared to their respective baseline. During adaptation to captivity process, B. jararaca heterophils phagocytic activity showed a positive correlation with serum corticosterone levels. However, the percentage of phagocytosis presented by azurophils and the quantity of particles ingested by lymphocytes, presented a negative correlation with serum corticosterone concentrations. For C. durissus, phagocytosis displayed by lymphocytes also presented a negative correlation with serum corticosterone levels. In both vipers species, oxidative burst activity showed no correlation with serum corticosterone concentrations. We believe that the data generated in this research will contribute to the development of new diagnostic tests, phylogenetic analyzes, ecotoxicological and ecoimmunological studies, as well as assisting in the clinic-sanitary management of snakes in captivity.